1994
DOI: 10.1159/000217903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Host-Organ Environment on the in vivo and in vitro Behavior of a Murine Mammary Adenocarcinoma

Abstract: We investigated the role that organ environment may play in determining the homing of disseminated cells from a murine mammary adenocarcinoma moderately metastatic to lung (M3). Conditioned medium (CM) from normal lung was able to enhance both local and metastatic growth. It increased the number of lung colonies when inoculated together with tumor cells via intravenous or separately via intraperitoneal route. Several in vitro studies were performed in order to elucidate possible mechanisms. It was shown that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…These results confirm previous data showing that lung-derived factors enhance the prolifer ation and migration in vitro, the local and metastatic growth in vivo [24] as well as the uPA activity [25] of M3 cells.…”
Section: Discussionsupporting
confidence: 92%
“…These results confirm previous data showing that lung-derived factors enhance the prolifer ation and migration in vitro, the local and metastatic growth in vivo [24] as well as the uPA activity [25] of M3 cells.…”
Section: Discussionsupporting
confidence: 92%
“…To assay their spontaneous metastatic ability, M3 and MM3 cells, harvested from subconfluent primary cultures during the exponential growth phase by treatment with Trypsin-EDTA, were washed thoroughly with MEM and resuspended in the same medium. Non-anesthetized BALB/c female mice were inoculated s.c. into the left flank with 2x10 5 viable cells of each tumor type, in a volume of 200 μl of serum-free MEM. Six weeks after inoculation animals were sacrificed and lungs were fixed in Bouin's solution.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the molecular requirements for some of these steps may be tissue specific. In fact, the proclivity that some tumors have for specific organs, such as breast carcinomas for bone and lung, was described more than a century ago and is still a matter of analysis (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that soluble factors from the lung, the target organ for the dissemination of the murine mammary adenocarcinoma cell line LM3, could enhance local and metastatic growth when inoculated together with the tumor cells intravenously or separately via intra peritoneal [59]. We also showed that the lung conditioned media stimulated in vitro growth and migration of tumor cells and secreted uPA activity in addition to enhancing angiogenesis in vivo [59][60][61]. Moreover, the microenvironment can exert a reprogramming effect.…”
Section: Growing In the Secondary Organmentioning
confidence: 91%